2002
DOI: 10.1366/0003702021955169
|View full text |Cite
|
Sign up to set email alerts
|

New Hybrid Algorithm for Maintaining Multivariate Quantitative Calibrations of a Near-Infrared Spectrometer

Abstract: Our newly developed prediction-augmented classical least-squares/partial least-squares (PACLS/PLS) hybrid algorithm can correct for the presence of unmodeled sources of spectral variation such as instrument drift by explicitly incorporating known or empirically derived information about the unmodeled spectral variation. We have tested the ability of the new hybrid algorithm to maintain a multivariate calibration in the presence of instrument drift using a near-infrared (NIR) spectrometer (7500–11 000 cm−1) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 10 publications
0
39
0
Order By: Relevance
“…In this case, y L ¼ 0. Similarly, key eigenvectors from the singular value decomposition (SVD) of L with samples containing constant or no analyte, such as spectra from repeatedly measuring the spectrum of a single sample [15,16], could be used for L with y L ¼ 0.…”
Section: Tr In 2-normmentioning
confidence: 99%
“…In this case, y L ¼ 0. Similarly, key eigenvectors from the singular value decomposition (SVD) of L with samples containing constant or no analyte, such as spectra from repeatedly measuring the spectrum of a single sample [15,16], could be used for L with y L ¼ 0.…”
Section: Tr In 2-normmentioning
confidence: 99%
“…Since the generalized ACLS algorithm is compatible with the PACLS method that allows rapid updating of models during prediction, the powerful combination of PACLS with ACLS is very promising for rapidly maintaining and transferring models for system drift, spectrometer differences, and unmodeled components without the need for recalibration. [4,5,161 The comparisons under different noise assumptions in the simulations obtained during this investigation emphasize the need to use realistic simulations when making comparisons between various multivariate calibration methods. Clearly, the conclusions of the relative performance of various methods were found to be dependent on how realistic the spectral errors were in the simulated data.…”
Section: Comparisons Of Prediction Abilities Of Augmented Classical Lmentioning
confidence: 95%
“…[I] In results published from this current LDRD project, we have demonstrated that the new hybrid algorithm can be used both to improve prediction abilities when instrument drift is present [2] and when transferring calibrations between spectrometers [3]. We demonstrated that the new hybrid method is very successful at maintaining and transferring multivariate spectral calibrations and that they performed as well or better than standard partial least squares (PLS) multivariate calibrations when calibration maintenance andlor transfer were required.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations